Teknik Desain User Interface dengan Wareframing untuk Rancangan Layout Website Perpustakaan Online Menggunakan Figma - Lutfiyani, Anisa; Sumantri, Riyan Jaya; Anggoro, Tri (Jurnal Kridatama Sains dan Teknologi, 2024)
Technological developments nowadays are increasingly developing day by day, it is important for agencies to understand user experience (UX) and user interface (UI) to support increased customer satisfaction. In this research, the researcher designed a user interface (UI) design wareframe, a web-based online library system design prototype using Figma, which aims to produce a flow concept in an attractive design wareframe design and implement the design results into a prototype. The focus of the research is designing the website user interface by looking at user needs. The method used in designing the User Interface (UI) uses the User Centered Design method so that the desired system interface can be achieved. The results of the research are the design of online library website user interface wareframing using Figma with a User Centered Design approach that can help find solutions according to the needs of target users. Based on the test results, it shows that the User Centered Website Design approach has succeeded in helping to make the Online Library website interface informative, interactive and communicative according to the needs of target users.